Peran Ekonomi Sosial Muhammadiyah dalam Membangun Kemandirian Umat: Tinjauan Konseptual dan Teoritis - Raden Muhammad Romadhon; Trya Ramadina HR; Reza Satria Hakim; Abdillah Subarkah, Milana (Penerbit Minhaj Pustaka, 2025)
This study examines the socio-economic contribution of Muhammadiyah in promoting community self-reliance through a qualitative literature-based approach. Data were derived from secondary literature spanning 2020-2025, including accredited journals, academic books, and institutional documents analyzed thematically. The research identifies three main findings: first, economic empowerment grounded in Islamic values such as ta'awun and social justice; second, institutional strengthening through Islamic microfinance institutions (BMT) and sharia cooperatives; third, challenges in integrating business enterprises and adopting digital technology. Theoretically, this study enriches the discourse on Islamic Social Capital within religious organizations, demonstrating the operationalization of spiritual values into a framework for community-based economic development. Practical implications include the need for institutional synergy, optimization of the Economic Council, and digitalization of governance. Further empirical research is recommended to validate the model contextually. Abstrak Penelitian ini mengkaji kontribusi sosial-ekonomi Muhammadiyah dalam mendorong kemandirian umat melalui pendekatan kualitatif berbasis studi pustaka. Data bersumber dari literatur sekunder periode 2020-2025, meliputi jurnal terakreditasi, buku akademik, dan dokumen kelembagaan yang dianalisis secara tematik. Hasil penelitian mengidentifikasi tiga temuan utama: pertama, pemberdayaan ekonomi berlandaskan nilai Islam seperti ta'awun dan keadilan sosial; kedua, penguatan kelembagaan melalui BMT dan koperasi syariah; ketiga, tantangan integrasi amal usaha dan adopsi teknologi digital. Secara teoretis, studi ini memperkaya diskursus Islamic Social Capital dalam konteks organisasi keagamaan, menunjukkan operasionalisasi nilai spiritual menjadi kerangka pembangunan ekonomi berbasis komunitas. Implikasi praktis mencakup perlunya sinergi kelembagaan, optimalisasi Majelis Ekonomi, dan digitalisasi tata kelola. Penelitian lanjutan dengan pendekatan empiris direkomendasikan untuk validasi model secara kontekstual.